Perpindahan Wali Nasab ke Wali Hakim Karena Wali Adhal dalam Penetapan Pengadilan Agama Kuningan No. 311/PDT P/2022/PA.kng: (Studi Perspektif Fiqih Muqoronah) - Hidayat, Yayat; Prasetya Ningrum, Indah (Sekolah Tinggi Ilmu Syariah Husnul Khotimah, 2024)
A marriage (parental) guardian is one of the legal requirements for marriage. Thus, any woman who marries without her guardian's permission is invalid. However, problems arise when the parental guardian is reluctant (adhal) to marry the prospective bride to the groom. The purpose of this research is to find out how the transfer of the parental guardian to the magistrate guardian is determined due to the guardian’s reluctancy (adhal) case number 311/Pdt.P/2022/PA.Kng. as well as Islamic law review on the judgment of the transfer of a parental guardian to a magistrate guardian due to the guardian’s reluctancy (adhal) based on the Fiqh Muqoronah perspective, case number 311/Pdt.P/2022/PA.Kng. This research uses a qualitative method with a descriptive data collection technique. The type of research used is field research. The data sources used are primary and secondary data sources. The data collection techniques used are interviews and documentation. The data analysis used is qualitative data analysis. The obtained data are then reduced, presented, and concluded using descriptive analysis techniques. The conclusions of the research are as follows: (1) Regarding case number 311/Pdt.P/2022/PA.Kng, the Kuningan Religious Court decided to grant the petitioner's request, by appointing the KUA (religious court) as magistrate guardian in place of the parental guardian due to the guardian’s reluctancy (adhal). Based on Islamic law, there is no prohibition between the petitioner and her prospective husband from getting married, because there is no mahram or consanguineous relationship between them. The solution is that these matters should be determined immediately to avoid problems that may arise. (2) Review of Islamic law regarding the judgment of the transfer of a parental guardian to a magistrate guardian due to the guardian’s reluctancy (adhal) based on the Fiqh Muqoronah perspective in the Study of the Judgment of the Kuningan Religious Court Number 311/Pdt.P/2022/PA.Kng, shows that it is in line with the Imam Madzhab, namely the Maliki Madzhab, Asy-Syafii, and Hanbali. According to the majority of Imam Madzhab, if the guardian refuses to marry the bride to the groom even though he is the mujbir guardian, then the magistrate guardian is the one who marries the bride to the groom. This is caused by a situation where the rights of guardian are attached to him, namely the petitioner's older brother, but his rights as guardian are terminated due to circumstances. Meanwhile, based on the perspective of the Hanafi Madzhab, in the case of a guardian’s reluctancy (adhal), it is like an invisible guardian. If the guardian is not present, then the guardianship rights are transferred to the ashabah guardian who has a further relationship according to the composition of the guardian.